Influência da variação de parâmetros de soldagem sobre a transferência metálica e perfil do cordão no processo MIG/MAG duplo arame - Groetelaars, Peter Jan (2005)
Double Wire MIG/MAG welding process appeared in manufacturing market as an alternative for metals joining, when highest productivity is demanded. However, the most important limitations of this process is the difficulty for parameter settings, as much because of doubled parameters in relation to the normal process as because each wire is dependent of each other. A better knowledge of this technology is fundamental to rule the process and its variables, aiming larger application in industry. With the intent of knowing more about this process, it was proposed this work with two approaches: a) a literature survey on basic operating knowledge and about the influence of the variables on metal transfer and weld bead profile; and b) an experimental evaluation to verify the influence of some variables on metal transfer and weld bead profile. Firstly, a methodology, based on a systematic variation of some parameters without the influence of the others, was proposed and evaluated, with the resulting analyses supported by metal transfer high-speed filming, electrical signal monitoring and weld bead profile measurements. The chosen variables for the experimental work were the arc length, the CO2 content in Ar based shielding gas, the distance between the wires in the torch, the torch attack angle and the ratio between wire feed speeds. The experiments were carried out always with the wire in sequence (leader and trail) and same mean current, total deposition rate and travel speed, so that comparisons could be done. According to the results, there is an ideal arc length, corresponding to the extent in which spray transfer begins. It was observed a strong attraction between drops from each wire ends, regardless the distance between the wires. This attraction turned critical for weldings with high CO2 content in the shielding gas. On the whole, the longer the arc and keeping the torch in a pushing position the wider and larger the beads. The deepest penetration was reached in a condition in which the speed of the wire leader was greater than of the trailing wire. A higher content of CO2 in the shielding gas led to increasing melted area, yet increasing also the arc instability, resulting in high material losses due to spattering.